clinical value of Serum iPTH , ALP and serum markers levels in patients with secondary hyperparathyroidism receiving paricalcitol combined with cinacalcet : clinical value of Serum iPTH and ALP levels - Lu, Xiaozhen (Journal of Medical Biochemistry, 2025)
Objective: The objective of this research is to investigate the impact of combining paricalcitol with cinacalcet on the concentrations of intact parathyroid hormone (iPTH) and alkaline phosphatase (ALP) in patients with secondary hyperparathyroidism who are undergoing maintenance hemodialysis (MHD). Methods: A retrospective review was performed on the clinical records of 129 individuals diagnosed with chronic kidney disease and secondary hyperparathyroidism who underwent maintenance hemodialysis in the hemodialysis unit from June to December 2022. The patients were divided into three cohorts according to their treatment approach: Group A (paricalcitol treatment; 43 cases), Group B (cinacalcet treatment), and Group C (combined paricalcitol and cinacalcet treatment). Hemoglobin (Hb), serum albumin (Alb), calcium (Ca), phosphorus (P), intact parathyroid hormone (iPTH), alkaline phosphatase (ALP), serum creatinine (Scr), and blood urea nitrogen (BUN) levels were assessed upon admission and at subsequent intervals of 1 day, 3 months, and 6 months for comparative evaluation across the three cohorts. Results: At 1 day post-hospitalization, the levels of hemoglobin (Hb) and serum albumin (Alb) in all three groups surpassed those in groups A and B (P＞0.05). Analysis of variance revealed significant differences in Ftime, Fgroup and F interaction (P＜0.05). Figure 2 (A, B) illustrates the comparison of calcium (Ca), phosphorus (P), and intact parathyroid hormone (iPTH) levels among the three cohorts. No statistically significant variances were detected in Ca, P, and iPTH levels across the three groups within 24 hours of admission (P＞0.05).Following 3 and 6 months of treatment, levels of Ca, P, and iPTH decreased across all groups compared to baseline (day 1), with Group C displaying the lowest levels relative to Groups A and B (P＜0.05). Significance was observed in Ftime, Fgroup and F interaction via analysis of variance (P＜0.05). Figure 4 (A-C) illustrates the comparison of alkaline phosphatase (ALP), serum creatinine (Scr), and blood urea nitrogen (BUN) levels among the three groups.No significant differences were found in ALP, Scr, and BUN levels among the three groups at 1 day post-admission (P＞0.05). Nevertheless, following 3 and 6 months of treatment, there was a decline in ALP, Scr, and BUN levels across all groups relative to those at day 1, with Group C demonstrating lower levels (P＜0.05).Repeated analysis of variance indicated significant differences in Ftime, Fgroup and F interaction (P＜0.05). Conclusion: The efficacy of paricalcitol combined with cinacalcet has been demonstrated in reducing levels of Hb, Alb, as well as Ca, P, and iPTH among individuals undergoing maintenance hemodialysis for secondary hyperparathyroidism.
Keywords: Paricalcitol; Cinacalcet; Maintenance hemodialysis; Chronic kidney disease; Hyperparathyroidism